Post-traumatic stress disorder (PTSD) in a sample of Hurricane Daniel affected in Derna in the light of some variables (Journal of Human Sciences, 2025)
The objective of the research is to identify the level of post-traumatic stress disorder in a sample of hurricane Daniel affected in Derna, indicating the differences in post-traumatic stress disorder in light of gender variables and scientific qualification, The descriptive curriculum (sample survey) through the use of a PTSD scale was based on a sample estimated at (674)  affected and damaged. The results resulted in a statistically significant post-traumatic stress disorder level in a sample of hurricane Daniel affected in Darna above the hypothesis, The existence of statistically significant differences in the aftermath of post-traumatic stress disorder (restoration of traumatic experience, avoidance of traumatic experience) and the overall scale score of a sample of Hurricane Daniel affected in Derna, depending on the sex variable (male, female) in the male direction, and the absence of statistically significant differences depending on the gender variable in the dimension (excitement), Lack of statistically significant differences in post-traumatic stress disorder (Restoration of traumatic expertise) and the overall grade of the scale according to the scientific qualification variable, and the existence of statistically significant differences in the dimensions of PTSD (Avoid traumatic experience, excitement) depending on the scientific qualification variable, and to see the direction of differences the Chevet test was used which showed that differences in the dimension (Avoid shocking experience) in the post-university direction, while in the aftermath (excitement) in the pre-university direction.